Does quality differentiation strategies enhance competitive advantage and customer satisfaction? a strategic management perspective / Arawati Agus and Za'faran Hassan - Agus, Arawati; Hassan, Za'faran (Institute of Quality & Knowledge Advancement (InQKA), 2005)
This study examines the impact of competitive quality differentiation strategies of Malaysian manufacturing companies and its impact on the enhancement of customer satisfaction. The findings demonstrate that consumer satisfaction can be influenced substantially by the product attribute structure, price and personnel differentiations. It also suggests that richer theories of competitive advantage may be constructed by formally integrating the "behavioral" view of consumer decision-making into concepts of marketing strategy.